Carbon Productivity’s Impact on Company's Financial Performance (Case Study of Companies Listed on IDX80 Stock Index) - Djie Liveren Adjie Tehananda; Robiyanto; Harijono Harijono (Journal of Management and Entrepreneurship Research, 2024)
Objective: Environmental issues are a concern, especially global warming. One of the consequences of global warming is a significant increase in carbon emissions each year. However, investors are trying to understand whether increased carbon also improves companies' financial performance. This study seeks to investigate the influence of carbon productivity on the company’s financial performance (case study of companies listed on the IDX80 index). Research Design & Methods: This research uses a quantitative method with secondary data taken from the company's annual and sustainability reports from 2020 to 2023. The sampling method used is the purposive sampling method. The sample used in this research was 80 companies listed on the IDX80 Index. Panel Data Regression Analysis is used to analyze the data. Findings: The findings of the study indicated carbon productivity has no significant effect on company financial performance, whether measured through ROA or MBR On the other hand, when control variables are added, they have a significant effect on the company's financial performance as measured through ROA. Implications and Recommendations: From these findings, stakeholders, investors and financial managers in the Indonesian capital market can help in making investment decisions, especially regarding the influence of carbon productivity on financial performance and for stakeholders. Contribution & Value Added: This study adds value to the practice of finance that seeks to see that companies that disclose higher carbon emissions will affect the company's financial performance in the context of developing countries, especially Indonesia.